PENERAPAN KARTU SMART MADANI SEBAGAI MEDIA AKSES PELAYANAN PUBLIK DI KOTA PEKANBARU - Andriyus, Andriyus; Nurhayati, Nurhayati (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2022)
This study aims to observe the implementation of the Smart Madani Card, a card that has many functions and as a medium for accessing public services to improve the quality of public services in the city of Pekanbaru. Improving the quality of public service delivery through the implementation of an electronic system that is developed into a service instrument by utilizing information technology through the media card, namely the Madani Smart Card. The application of the Madani Smart Card is one of the efforts of the Pekanbaru city government to accelerate the realization of a Madani Smart City. Smart City is a Smart City that integrates technology and communication in governance to increase efficiency, share information with the public so as to improve the quality of public services. The method used in this research is descriptive qualitative with purposive sampling technique and snowball sampling. The data collection techniques used were interview, observation and documentation techniques. Based on the methods and techniques used by the author in the study, the researcher assessed and concluded that the implementation of the Smart Madani Card was not well implemented.